A self-positioning linear actuator based on a piezoelectric slab with multiple pads. (March 2021) - Wang, Yu-Jen; Ho, Jie-Lin; Jiang, Yi-Bin
Highlights: Using multiple pads provides long driving region that is 85% of actuator length. Based on Hammerstein–Wiener model to estimate nonlinear kinematic behavior of the actuator. Guard electrodes collimate the electric field lines in a capacitive position sensor to enhance S/N. Velocity-adaptive Kalman filter is used to estimate the capacitive signal. A compacted-sized and low-cost actuator provides accuracy of 25 μm in vertically upwards. Abstract: A component-less, long-driving-region and self-positioning piezoelectric actuator was developed to transmit several gram-weight components. The linear piezoelectric actuator was composed of a piezoelectric slab and comb-shaped capacitive position sensor. The length-to-width ratio of the driving pad was designed to ensure successive in-phase connection when the driving pad was subjected to an electric field. The proposed 44 × 8 × 1.5 mm 3 piezoelectric slab had a driving region of 37.5 mm, that is, 85% of the length of the actuator larger than previous studies to save space. Two pairs of capacitive comb-shaped electrodes were screen-printed on a slider clip (mover) and piezoelectric slab (stator) to sense the position of the slider clip. Sensing electrodes abreast of guard electrodes are proposed to collimate the electric field lines and reduce noise. The kinetic model of the driven clip was based on a frictional driving equation revised using the Hammerstein–Wiener model to capture the nonlinearities and dynamic behavior variations with the duty ratios of driving signals. According to the kinetic model, the control strategies were decided and the velocity of the slider clip at any position could be estimated. Based on the velocity estimated using the Hammerstein–Wiener model, a velocity-adaptive Kalman filter was proposed. The prototype generated a maximum velocity of 18.9 mm/s, a mean steady-state error of 25 μm, and a settling time of 2.29 s for a 2.2 g weight driven vertically upwards to a distance of 25 mm.